1990
DOI: 10.1073/pnas.87.3.867
|View full text |Cite
|
Sign up to set email alerts
|

G-DNA: a twice-folded DNA structure adopted by single-stranded oligo(dG) and its implications for telomeres.

Abstract: Our dimethyl sulfate modification experiments suggest that (dG). stretches within single-stranded DNA fragments, which represent the simplest model for telomeric sequences, adopt a complex intrastrand structure other than a simple hairpin. We present a molecular model for the DNA structure that conforms to dimethyl sulfate methylation data. The principal element of this G-DNA structure is a quadruple helix formed by pairwise antiparallel segments of the twicefolded (dG). stretch. This quadruple core has two wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 24 publications
1
47
0
1
Order By: Relevance
“…These G-rich tracts form self-association complexes involving other than Watson-Crick hydrogen bonding patterns. Both solution (12) and solid state (13) studies have revealed that these sequences can form stable-structures with Hoogsteen-type hydrogen bonded guanine tetrads (G4), not only by intermolecular association of four different strands (14), but also by intermolecular association oftwo hairpins (15) or even by intramolecular folding of a single-strand (16).…”
Section: Introductionmentioning
confidence: 99%
“…These G-rich tracts form self-association complexes involving other than Watson-Crick hydrogen bonding patterns. Both solution (12) and solid state (13) studies have revealed that these sequences can form stable-structures with Hoogsteen-type hydrogen bonded guanine tetrads (G4), not only by intermolecular association of four different strands (14), but also by intermolecular association oftwo hairpins (15) or even by intramolecular folding of a single-strand (16).…”
Section: Introductionmentioning
confidence: 99%
“…This intriguing structural motif was proposed some time ago based on fiber diffraction studies (2)(3)(4) and only recently has been rediscovered. This rekindled interest has been fueled, in part, by the recognition that telomeres, the 3' single-stranded guanine-rich overhangs found at the termini ofchromosomes, (5)(6)(7)(8) may form G-DNA type structures of potential biological significance (1,(9)(10)(11)(12)(13)(14). In addition to their presence in telomeres, where they may play a role in maintaining the stability and integrity of chromosomes (8), guanine-rich regions also are found within recombination and mutation hot spots (15)(16)(17)(18)(19) and in gene regulatory regions (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Guanine-rich regions can form G-tetrad-containing structures monomolecularly via intramolecular folding (11,13,14,25), bimolecularly by association of two hairpins (11,12,25,26), or tetramolecularly by alignment of four separate strands (10,(27)(28)(29)(30)(31)(32)(33)(34)(35). An examination of the literature reveals examples of tetrad-containing structures from each of these three classes, including, in some cases, superstructures formed by their aggregation (31,33).…”
mentioning
confidence: 99%
“…Earlier reports have also appeared describing parallel four-stranded structures for poly(G) and poly(I) (12). In the last 5 years, several telomeric sequences have been studied using physical and structural methods (13)(14)(15)(16)(17)(18). Henderson et al (15) have examined a variety of sequences with enhanced electrophoretic mobility that exhibited low-field exchangeable protons in the NMR spectra, indicating the presence of GIG base pairing.…”
mentioning
confidence: 99%